Adoptive T Cell Immunotherapy for Treatment of Ganciclovir‐Resistant Cytomegalovirus Disease in a Renal Transplant Recipient. Issue 3 (3rd February 2015) - Macesic, N.; Langsford, D.; Nicholls, K.; Hughes, P.; Gottlieb, D. J.; Clancy, L.; Blyth, E.; Micklethwaite, K.; Withers, B.; Majumdar, S.; Fleming, S.; Sasadeusz, J.
<x xml:space="preserve">Abstract</x> Cytomegalovirus (CMV) is a significant cause of morbidity, mortality and graft loss in solid organ transplantation (SOT). Treatment options for ganciclovir‐resistant CMV are limited. We describe a case of ganciclovir‐resistant CMV disease in a renal transplant recipient manifested by thrombotic microangiopathy‐associated glomerulopathy. Adoptive T cell immunotherapy using CMV‐specific T cells from a donor bank was used as salvage therapy. This report is a proof‐of‐concept of the clinical and logistical feasibility of this therapy in SOT recipients.